UMPSA celebrates students’ success in receiving Chinese Ambassador’s Excellence Award - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 10 February 2025 – A total of 14 students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently received the Chinese Ambassador’s Excellence Award from the Embassy of China at the Executive Lounge, UMPSA Library, Pekan. The Deputy Vice-Chancellor (Academic and International Affairs) of UMPSA, Professor Dato’ Ir. Ts. Dr. Ahmad Ziad Sulaiman, representing the Vice-Chancellor of UMPSA, Professor Dr. Yatimah Alias, welcomed the delegation from the Embassy of China, including Education Counsellor, Zhao Changtao, and Education Secretary, Tang Jing.